Innovation in the Development of Batik Motifs Using Iron Stamps and Wax in Small and Medium Industries (SMIs) Batik Lambur 1 - Reni Ardwiyanti; Zaenal Abidin; Kurniawan; S Idris; Raden AH (CV. Zabags Qu Publish, 2025)
This study examines the innovation of batik motif development through the application of iron stamps combined with wax at the Small and Medium Enterprise (SME) Batik Lambur 1 as a strategy to enhance production efficiency and motif accuracy. The research is motivated by challenges faced by local batik industries, limited tools, lengthy production times, and the need to maintain motif quality and consistency amid intensifying market competition. A qualitative phenomenological approach was employed to explore the lived experiences of production actors and university student mentors involved in implementing the stamping technique. Data were collected via participant observation, in-depth interviews, and process documentation, and were analyzed thematically using interpretative phenomenological analysis. Findings indicate that the iron-stamp and wax technique improved motif precision, reduced printing errors, and shortened production time per unit, while student involvement strengthened process documentation and workflow management. The study contributes theoretically to the understanding of open innovation and capability transformation within culture-based creative industries, and offers a practical collaborative model between academia and industry to support sustainable, context-appropriate production innovation in local batik SMEs.